Deep-sea (>1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species - Mah, Christopher L. (Zootaxa, 2016)
Research cruises by the Monterey Bay Aquarium Research Institute (MBARI) have resulted in the discovery of three new species of asteroids from the lower bathyal/abyssal regions of the North Pacific. A new genus, Bathyceramaster is described to accommodate “Mediaster” elegans Ludwig 1905 and related species. New records and in situ observations are also presented. An identification key and taxonomic account of the deep-sea Goniasteridae known from this region including one new genus and two new species is included. An overview of the genus Sibogaster, including a new widely occurring species, is also included.